Encapsulating plant ingredients for dermocosmetic application: an updated review of delivery systems and characterization techniques - Yang, S.; Liu, L.; Han, J.; Tang, Y. (International journal of cosmetic science, 2020)
Today, there is a rising demand and ongoing search for novel plant‐derived phytochemicals in the cosmetic market owing to the growing consumer expectations worldwide for green and natural health products. Various plant ingredients, including polyphenols, oils, volatile oils, vitamins and other herbal extracts, have been extensively used in herbal cosmetics. Recent advances in encapsulation technologies have greatly improved their chemical stability, biocompatibility, skin permeability and dermocosmetic efficiency when applied topically. This comprehensive review summarizes the up‐to‐date information on encapsulated plant ingredients tailored for dermocosmetic application with a focus on the development of novel delivery systems. An overview of the commonly used techniques for carrier characterization, performance‐related properties and toxicological evaluation is also included, which might provide guidance for researchers to select or develop appropriate assay systems. Résumé Aujourd'hui, face aux attentes croissantes des consommateurs à travers le monde pour les produits écologiques et naturels, la demande et les recherches sur les nouveaux ingrédients phytochimiques d’origine végétable augmentent de façon substantielle sur le marché des cosmétiques. Divers ingrédients végétaux, notamment des polyphénols, huiles, huiles essentielles, vitamines et d’autres extraits de plantes, ont été largement utilisés en cosmétique à base de plantes. La stabilité chimique, la biocompatibilité, la perméabilité cutanée et l’efficacité dermo‐cosmétique ont été considérablement améliorées grâce aux derniers progrès des techniques d’encapsulation, lorsqu’elles sont appliqués par voie topique. Cet examen complet résume les informations les plus récentes sur les ingrédients végétaux encapsulés utilisés pour une application dermo‐cosmétique en se concentrant sur le développement de nouveaux systèmes de libération. Le rapport fournit également un aperçu des techniques couramment utilisées pour la caractérisation des supports, les propriétés liées aux performances et l'évaluation toxicologique, ce qui pourrait guider des chercheurs dans la sélection ou la mise au point de systèmes de dosage appropriés. This article begins with a critical review of popular plant ingredients encapsulated for dermocosmetic application and the commonly employed delivery systems. An overview of the current scientific approaches to the characterization of carrier system and performance‐related properties is also included, which may provide guidance for researchers to select or develop appropriate assay systems.